The Great Gap : Inequality and the Politics of Redistribution in Latin America - Blofield, Merike (Book collections on Project MUSE., 2011)
"A collection of essays addressing the relationship between inequality and politics in Latin America. Examines the socioeconomic context and inequality of opportunities; elite culture, public opinion, and media framing; capital mobility, campaign financing, representation and gender equality policies; and taxation and social policies"--Provided by publisher.